Investigating the factors that influence higher education instructors' decisions to adopt a flipped classroom instructional model. (4th October 2018) - Long, Taotao; Cummins, John; Waugh, Michael
Abstract: The flipped classroom is an instructional model which allows for more advanced learning activities during in‐class time while introduces subject knowledge to students prior to class. To address a gap in the recent research regarding higher education instructors' experiences, perceptions and adoption decisions of the flipped classroom instruction, this study aimed at investigating the critical factors which were predictive of a higher education instructor's decision to adopt a flipped classroom instructional model through exploratory factor analysis (EFA) and multiple regression in a US university. The results revealed that performance expectancy and technology self‐efficacy were significant predictors. Although facilitation condition was significantly correlated with instructors' adoption decisions, it was not a significant predictor. This study suggests that in order to improve higher education instructors' adoption decisions of the flipped classroom and other active learning instructional models, it is of priority for institutions to remove the internal barriers to instructors' adoption decisions of these instructional models, such as improving their performance expectancy and technology self‐efficacy.